Penerapan Media Mind Mapping terhadap Hasil Belajar Peserta Didik pada Pembelajaran Biologi Kelas XI SMAN 01 Sungai Geringging - Putri Andayani; Diana Susanti; Vivi Fitriani (Departement of Mathematics Education, 2023)
In this experimental research to see the application of mind mapping media to student learning outcomes. This type of research is quantitative with experimental nature (Randomized Control Group Only Design). There are 2 classes of samples, namely class XI Mia 2 and XI Mia 3. The sampling technique was purposive sampling. The instrument is in the form of objective questions that have been validated. The average result of the sample class has increased. In the cognitive aspect, it has increased from previous learning outcomes but still has not reached KKM. Because in the application of the technique there are advantages and disadvantages.